Методичні підходи до оцінювання ціни конкурсних пропозицій: надбання та недолік - Мацапура, О. В. (Видавництво Львівської політехніки, 2015)
Узагальнено методичні підходи до оцінювання ціни конкурсних пропозицій. Визначено переваги та недоліки кожної з них. Надано пропозиції для усунення виявлених недоліків та визначення методики, найприйнятнішої саме для будівельних підприємств. Зазначено, що мета оцінки пропозицій полягає у визначенні рейтингу прийнятних по суті оферт для того, щоб виявити найвигіднішу для закупівельника пропозицію, визначивши витрати для кожної з них так, щоб мати можливість швидко та достовірно порівняти їх. Вибір найприйнятнішої методики оцінювання конкурсної пропозиції дає можливість визначити доцільність участі оферента у торгах, запропонувати найконкурентоспроможнішу ціну й оцінити ймовірність отримання вигідного підряду. Currently there are quite a number of methods for evaluation of price bids: ball, lowest price, estimated cost, low technical specifications, life cycle cost, cost, administrative and other. The analysis of these methods allows you to choose the most effective for each individual case (the level of competition, cost, timing). At the moment this procedure as the tender is widely distributed in a competitive construction market. In order to choose the winner of the tender should evaluate which of the bidders have put forward the best offer. There are various methods of evaluation of offers, the analysis techniques will allow you to choose the most effective. This paper summarizes the methodological approaches to the evaluation of the price bids, аdvantages and disadvantages of each. Proposals to address the identified weaknesses and the definition of the methodology that best suits the construction companies. The purpose of bid evaluation is to determine the acceptable rating on the merits of offers to identify the most profitable for the buyer suggestion by determining the costs of each of them in such a way as to be able to quickly and accurately compare them. The basic principle of correct assessment: take into account only the factors specified in the tender specifications, to consider them only on the basis of the criteria stated in the tender documents. Techniques of bids in construction. Point. Evaluation of each proposal by awarding her the appropriate number of points. Taking into account coefficients of various factors. Lowest price. The sole criterion in the consideration of offers is price. With preference given to the proposal with the lowest price. Estimated cost. The main criterion is the estimated value. Preference is given to the proposal with the lowest estimated cost. The minimum technical specifications. Selected proposals with the minimum technical specifications. Preference is given to the proposal with the lowest estimated cost. The life cycle cost. The initial price and the cost of operation and maintenance, which determines the total cost of the offer. Costly. Focuses on costs and desired profit. Administrative. Focus on the prices of the main competitors, or focus on one competitor – price leader. Thus the choice of the most appropriate methods for the assessment of proposal prices provides an opportunity to determine the appropriateness of the оffer or in the auction to offer the most competitive price and to assess the likelihood of favorable contract.
Methodological approaches to evaluation of price bids: achievements and shortcomings
Keywords: ціна конкурсної пропозиції; мінімум технічних специфікацій; вартість життєвого циклу; оціночна вартість; найменша ціна; бальна; адміністративна; витратна методики; price bids; ball; min technical specifications; life cycle cost; estimated cost; the lowest price administrative; costly techniques